Comparing the acoustic expression of emotion in the speaking and the singing voice. (January 2015) - Scherer, Klaus R.; Sundberg, Johan; Tamarit, Lucas; Salomão, Gláucia L.
Highlights: Acoustic analyses of emotional singing show significant differences between 10 emotions. Loudness, tempo, spectral balance and perturbation differentiate emotions most. Patterns for singing are very similar to those found for actors' speech portrayals. Singers tend to rely more than actors on the use of voice perturbation, specifically vibrato. Abstract: We examine the similarities and differences in the expression of emotion in the singing and the speaking voice. Three internationally renowned opera singers produced "vocalises" (using a schwa vowel) and short nonsense phrases in different interpretations for 10 emotions. Acoustic analyses of emotional expression in the singing samples show significant differences between the emotions. In addition to the obvious effects of loudness and tempo, spectral balance and perturbation make significant contributions (high effect sizes) to this differentiation. A comparison of the emotion-specific patterns produced by the singers in this study with published data for professional actors portraying different emotions in speech generally show a very high degree of similarity. However, singers tend to rely more than actors on the use of voice perturbation, specifically vibrato, in particular in the case of high arousal emotions. It is suggested that this may be due to by the restrictions and constraints imposed by the musical structure.